Mapping the Serious and the Dangerous: Film and the National Council of Education, 1920-1939 - Acland, Charles (Cinémas)

(untitled) (Cinémas, 1995)
This article recognizes the National Council of Education's tole in articulating the national educationalist objective for Canadian film. The NCE was a significant force; it was a powerful lobby, initiator of cultural activities, and producer of cultural criticism. The NCE was imperialist in orientation, and took as one of its goals the improvement of popular taste. Its members encouraged the regulation of recreation and modes of popular pleasure so that leisure time served the nation. This educationalist agenda led them to promote documentary film and to write about the dangers of popular cinema, both of which find their way into later developments in Canadian film policy.